Identifying the transnational and transcultural aesthetics of Chinese diasporic art in Singapore : a study of Cheong Soo Pieng's works and experiences - Goh, Anne Jia Juan (Nanyang Technological University, 2021)
This paper investigates Chinese diasporic modern art in Singapore through analysing Cheong Soo Pieng's (Xiamen, 1917 — Singapore, 1 July 1983) works and experiences before and after relocating from China to Singapore in 1946. Despite the extensive scholarship on the patterns of Chinese emigration and on the adaptation and behaviour of diasporic Chinese, there has been comparatively lesser attention directed to the examination of diasporic Chinese art practices globally, with existing research mainly focusing on diasporic Chinese contemporary art. Diasporic Chinese modern art globally remains overlooked, with only a few exceptions. The objective of this study is to consolidate the social, political and cultural complexities that diasporic Chinese artists have to navigate to forge their transcultural identities and transnational visual lexicons, and also to contribute to a more comprehensive understanding of Southeast Asian modern art history. The history of art goes in tandem with the progress of society. The emphasis in this paper was to think about the epoch and the glocal circumstances in which an artwork was produced. Using the artist's travels as departure points, and then breaking the artist's oeuvre into thematic sections, while concurrently drawing in different social, political and cultural contexts, this three- pronged approach creates a structured and systematic methodology that can be utilised for the interdisciplinary study of Chinese diasporic art practices. Using this approach, this study examines the multifaceted inspirations from which Cheong derived his imageries — Chinese, Japanese and Western painting aesthetics, Chinese oracle bond script, wayang kulit, different religions, motherhood, Po Mo splashed ink painting style, primordial chaos, colour field painting and geometricism. This inquiry demonstrates how Cheong merged various diverse influences to formulate his own hybrid identity. Adeptly navigating the complex intricacies of these influences enabled him to achieve a unique transnational and transcultural pictorial language.